Effective response metric (ERM-D8) using time-series gene expression profiling at diagnosis and day 8 of remission-induction therapy is a novel early prognostic marker to predict relapse in childhood acute lymphoblastic leukemia (ALL) - a Malaysia-Singapore all study - Yeoh, A.E.J.; Li, Z.; Dong, D.; Lu, Y.; Trka, J.; Kham, S.K.Y.; Tan, A.M.; Ariffin, H.; Wong, L.S. (American Society of Hematology, 2014)
BACKGROUND